Current State of Care for Pediatric ACL Ruptures in the Netherlands: A Survey - Dietvorst, Martijn; Reijman, Max; van Zutven, Rein; van den Bekerom, Michel P. J.; Meuffels, Duncan E.; Somford, Matthijs P.; Janssen, Rob P. A. (The Journal of Knee Surgery, 2019)
The management of anterior cruciate ligament (ACL) injuries in the skeletally immature patient is an area of controversy. The purpose of this survey is to inventory the current state of care for pediatric ACL injuries in the Netherlands. This survey was conveyed by e-mail among all members of the Dutch Arthroscopy Society (Nederlandse Vereniging van Arthroscopie [NVA]) and promoted on the Web site of the NVA. It was developed by the scientific committee of the NVA by a consensus meeting discussing relevant topics in pediatric ACL injuries. All members of the NVA received the survey (n = 540). A total of 158 (29%) members responded to the survey, of which 143 were completed. A total of 126 responses were analyzed after exclusion. The main finding of this survey is that 78% of the respondents tend to treat children with open physes nonoperatively, while 65% tend to treat children with closed physes operatively. The most frequently performed procedure is the transphyseal reconstruction. Many considerations were involved in choosing operative treatment. The postoperative follow-up period varies from less than 1 year (24%) until fully grown (27%). In conclusion, this survey shows that the current state of care for pediatric ACL injuries is variable and a matter of debate in the Netherlands. Although the response rate seems low, this survey provides an overview of the opinions of specialized orthopaedic surgeons in the Netherlands. The results of this survey led to the development of the national registry for pediatric ACL in the Netherlands. The level of evidence for this study is V.
Keywords: anterior cruciate ligament; pediatric; physeal sparing; transphyseal; survey